Avaliação do "magnetron sputtering" como técnica para obtenção de MgB2 - Almeida, Manoela Adams de (2014)
In this work a survey of the potentialities and limitations of magnetron sputtering as a tool for the production of MgB2 superconductors thin films has been made. Instead of the usual approaches, like co-deposition onto heated substract or room temperature deposition of MgB multilayers for ex situ annealing, the direct deposition of multilayers onto heated substract has been tested. The samples have been deposited onto Si waffers from Mg and B targets. They have been produced by the alternated grown of Mg and B layers, holding the substrate temperatur at 200 and 300 C during the depostion. Pos deposition annealings were performed at temperatures rangingo from 560 up to 800. In order to improve the sticking coefficient of Mg atoms at the substrate, the ayers thicknesses were held under ten monoatomic layers. The composition and structural properties were determined by X-Ray diffraction. The results have shown that, for the used temperatures, the Mg sticking coefficient onto B is just relevant ultil the second or third Mg monoatomic layer is completed. From this point, all Mg atoms impinging the substrate are re-emmitted to the chamber atmospherre. As a consequence, the direct production of MgB2 from the sucessive deposition of B and Mg are not effective, unless the layers thicknesses do not surpass a few tenths of nanometers.